STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU MELALUI PROGRAM UNGGULAN STUDI KASUS DI SMAN 2 PAGADEN KABUPATEN SUBANG, JAWA BARAT (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The school principal plays a key role in improving or enhancing the quality of educational units. Various strategies can be applied to enhance quality in educational units, one of which is through the implementation of superior programs, as carried out by the principal of SMAN 2 Pagaden. The objectives of this research are to describe the process of implementing superior programs, to analyze the impact of implementing superior programs on improving the quality of the educational unit, and to identify the inhibiting factors in implementing superior programs at SMAN 2 Pagaden. The type of research is qualitative, using methods of observation, interviews, documentation, and field observations. Based on the research results conducted by the researcher, SMAN 2 Pagaden has various superior programs, including morning routines, the principal's greeting program, outing campus, career guidance, monitoring of teaching and learning activities, learning communities and etc. The implementation of superior programs at SMAN 2 Pagaden begins with the planning stage, organization, implementation, and evaluation/follow-up. The implementation of superior programs at SMAN 2 Pagaden has positive impacts, including creating school programs that are student-centered, increasing the number of graduates who continue to higher education, improving school facilities and infrastructure, enhancing student achievement, and fostering collaboration with various school stakeholders. Meanwhile, the obstacles or challenges faced in the process of implementing superior programs at SMAN 2 Pagaden include limitations in human resources to drive activities, conservative attitudes from some parents and teachers at SMAN 2 Pagaden, and low management of monitoring for superior programs.